Bidimensional Sturmian basis for bound states and collision problems. Issue 13 (January 2020) - Randazzo, J M; Ancarani, L U
Synopsis: We present a novel spectral approach to deal both with bound states and with stationary continuum waves associated to collision problems. It is based on the definition of a two dimensional radial basis which replaces the combination of single particle basis sets as employed in most of the usual spectral methods. The new basis elements are externally defined as solutions of a generalized Sturmian eigenvalue equation containing the main properties of the physical problem under consideration.